Analysis of Damage to Main Bearing on The Diesel Generator Motors at KM Sabuk Nusantara 89 - Apriliani, Apriliani; Mursidi, Mursidi; Yanti, Dyah Agustin Widhi (Universitas Hang Tuah, 2024)
Main bearings are made from special metal materials that are resistant to hot engine friction. The main bearing has holes in several parts which function to allow fluid (lubricating oil) to flow. Metal sitting is two plates that have a very smooth surface and consist of several layers of metal that have different hardness. The main bearing is a very vital part to support the performance of the crankshaft. The aim of this research is to determine the factors that cause damage to main bearings in diesel generator motors. The research method used is a qualitative descriptive method using observation, interviews and documentation methods and using the fishbone analysis method. The results obtained from this research show that the causes of damaged main bearings in diesel generator motors are decreased lubricating oil pressure, lack of understanding of maintenance procedures and fatigue of the seated metal component materials.